أثر جودة البنية التحتية لتكنولوجيا المعلومات والاتصال على جذب الاستثمار الاجنبي المباشر خلال الفترة 2007-2021 - جودي بوعمرة; ضويفي حمزة (جامعة الوادي University of Eloued, 2024)
The study aims to identify the causal relationship between information technology and communication infrastructure and foreign direct investment. Hence, it focuses on the model that explains the relationship using Panel data of a group of Arab countries during (2007-2021) Processing it with Eviews 10. Findings show that there is no causal two ways relationship between the study variables. Therefore, both variables have no relationship in the short term. However, the interpretation coefficient between the two variables reached 65% and 79% respectively. Thus, the model that explains the relationship between the study variables is the VAR model.
The impact of the quality of information and communication technology infrastructure on attracting foreign direct investment during the period (2007-2021)
Keywords: بنية التحتية; تكنولوجيا المعلومات والاتصال; الاستثمار الاجنبي المباشر